Bank loan loss provisions research: A review of the empirical literature - Oryza Sativa Heningtyas; Ari Kuncara Widagdo (Jurnal Keuangan dan Perbankan, 2019)
This paper aims to provide an overview of the literature on Loan loss provisions in the Banking industry. This research was conducted by reviewing some literature. LLP is a solution for banks to deal with risks that will be faced by banks or as a prudent banking principle. We have reviewed and mapped the literature in several sections, developments in the Basel Regulations, mapping LLP literature based on the research area, and LLP and hypothesis mapping. The main fact that we reveal is that most banks use LLP regulations for various purposes. This paper relies on the literature and highlights information as well as important issues related to LLP in the research field, this study highlights several important issues related to the banking industry in various countries. This study observed the role of LLP during the application of Basel III regulation which tended to provide flexibility to bank managers in determining provision reserves. We have reviewed the specific LLP literature in one country and cross-country research. This study identifies gaps and provides direction that can be used as a research contribution in the future.JEL Classification: G1, G2, G4DOI: https://doi.org/10.26905/jkdp.v23i2.2835